(untitled) (Journal of Science and Technology, 2016)
Phytochemical investigation of the ethanol extract of the whole plant of Scoparia dulcis, has resulted in the isolation of 4, 5, 7-trihydroxy-6-methoxyflavone, commonly called hispidulin and a steroidal glycoside, β-sitosterol-β-D-glucoside. This is the first isolation of the two compounds from S. dulcis. Also isolated and characterized were the previously reported 6-me-thoxybenzoxazolinone, friedelan-3-one and scopadulcic acid B. Structural elucidation was done on the basis of spectroscopic data interpretations (IR, UV, NMR and EIMS). Using the Tetrazolium-based colorimetric selective assay, hispidulin was found to be inactive against HIV-1/IIIB in MT-4 cells whereas the same test on the aqueous extract of the plant was positive.